Varasi Konsentrasi Enzim Stargen TM 002 Pada Proses Sakarifikasi Dan Fermentasi Serentak Pati Sorgum Menjadi Bioetanol - Dike Putra Ganda; Chairul Chairul; Hafidawati Hafidawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
One of the plants that can be used as raw material for making bioefuel as alternative energy is sorghum. Grain sorghum has a high starch content that can be used as a substrate for the production of bioethanol. This study aims to determine the concentration of the enzyme and the best time of fermentation to produce bioethanol. The research method using the simultaneous saccharification and fermentation (SSF) with the aid of enzymes Stargen ™ 002 and the yeast Saccharomyces cereviceae. Variations made to the enzyme concentration Stargen ™ 002 is used as follows: 2.5%, 3%, 3.5% and 4% and fermentation time for 30, 36, 42, 48, 54, 60, 66 and 72 hours. Analysis of the results using the Alcoholmeter with highest bioethanol yield at 4% enzyme concentration at 42 hours of fermentation with ethanol content of 8% (v / v) Keywords: Sorghum, Bioethanol, Stargen™ 002 Enzymes, Enzyme Concentration, SSF